Analysis of the Influence of Financial Literacy on Financial Behavior Using Financial Technology as an Intervening Factor for Mekaar PNM Customers - Melki Bobby Veronica; Acong Dewantoro Marsono (PT FORMOSA CENDEKIA GLOBAL, 2023)
Madani National Capital (PNM) was established as an effort taken by the government to become a financial management institution in advancing, maintaining and developing Micro, Small and Medium Enterprises (MSMEs). PNM is an institution that provides training for micro-entrepreneurs and is a strategic solution for the government to develop access to capital throughout Indonesia. PNM is expected to be able to become a financial institution that can create independent and resilient customers with one hundred percent of the shares held by the government. Financial literacy can be understood as knowledge, skills and beliefs that influence attitudes and behavior to improve the quality of decision making and financial management in an effort to achieve prosperity. Simply put, financial literacy is the ability to understand and apply effectively a wide range of financial skills, including personal finance management, budgeting and investing. A strong financial literacy foundation can support various life goals, such as saving for education and retirement, managing money productively, running a business, and being selective and using debt responsibly. People who have a high level of financial literacy, meaning they are financially literate, so they are not too vulnerable to financial fraud. Conversely, people with low financial literacy are referred to as people who are financially illiterate, so they are easily influenced and trapped in financial fraud. In conducting this research, the population was all Mekaar PNM customers in 5 Mekaar PNM units, 3 units in urban areas and 2 units in rural areas, totaling 15,549 customers